ADVANCED FOREIGN EXPERIENCE IN TEACHING CIVIL PROTECTION IN EMERGENCY SITUATIONS (Scientific journal of the Fergana State University, 2023)
This article provides information on foreign experience in teaching civil protection in emergencies and how civil defense work is organized in these countries.